The Routledge International Handbook of English, Language and Literacy Teaching - Wyse, Dominic, Ed; Andrews, Richard, Ed; Hoffman, James, Ed (Routledge, Taylor & Francis Group, 2010)
Edited by three authorities in the field, this "Handbook" presents contributions from experts across the world who report the cutting-edge of international research. It is ground-breaking in its holistic, evidence-informed account that aims to synthesize key messages for policy and practice in English, language and literacy teaching. A comprehensive collection, the "Handbook" focuses on the three key areas of reading, writing, and language, and issues that cut across them. The international emphasis of all the chapters is extended by a final section that looks directly at different countries and continents. The authors address many key issues including: (1) why pupil motivation is so important; (2) the evidence for what works in teaching and learning; (3) the place of Information Technology in the twenty-first century; (4) the status of English and other languages; and (5) globalisation and political control of education. This definitive guide concludes by discussing the need for better policy cycles that genuinely build on research evidence and teachers' working knowledge in order to engage young people and transform their life chances. Part I, Reading Social and Cultural Influences on Children's Motivation for Reading, contains the following: (1) Literature for Children; (2) Approaches to Teaching Literature; (3) Reading and Teaching Short Stories, Based on Process Studies and Experimental Research; Comprehension Instruction: Merging Two Historically Antithetical Perspectives; (4) The Genre-Specific Nature of Reading Comprehension; (5) Morphological Knowledge and Learning to Read in English; (6) Phonological Development Across Different Languages; and (7) Interaction and Learning to Read: Towards a Dialogic Approach. Part II, Writing Facilitating Writing Development, contains the following: (8) Writing in the Early Years; (9) The Ontogenesis of Writing in Childhood and Adolescence; (10) Composition Across Levels of Schooling: Cognitive, Textual and Social Dimensions; (11) Rhythm And Blues: Making Textual Music with Grammar and Punctuation; (12) Linguistic Foundations of Spelling Development; and (13) Handwriting and Writing. Part III, Language Orality, Literacy, and Culture: Talk, Text, and Tools in Ideological Contexts, contains the following: (14) Understanding Language Development; (15) Bilingualism and English Language Teaching; Drama-Teaching, Learning, Language and Literacy; and (16) Classroom Discourse: Towards a Dialogic Pedagogy. Part IV, Teaching English, Language and Literacy Critical Approaches to Teaching Language, Reading and Writing, contains the following: (17) Culturally Responsive Teacher Preparation: Learning in Field Experiences for Prospective Literacy Educators; (18) The Text Environment and Learning to Read: Windows and Mirrors; (19) Shaping Literate Lives; (20) The Relationship Between Home And School; (21) Literacy Practices; (22) Gender and the Teaching of English; (23) An Outward, Inward, and School-ward Overview of Interactive Communication; (24) Technologies Across the Literacy Landscape; (25) Multimodality, Literacy and School English; (26) A Very Long Engagement: English and The Moving Image; (27) Reading, Writing and Speaking Poetry; (28) Teaching Shakespeare; (29) Difficulties in Learning Literacy; (30) Classroom Assessment; and (31) Initial Teacher Preparation for Reading Instruction. Part V, English, Language and Literacy Teaching: Countries as Contexts International Comparisons of Literacy--What have they revealed?, contains the following: (32) Globalisation and the International Context for Literacy Policy Reform; (33) A Tale of the Two Special Administrative Regions (SARS) of China--An Overview of English Language Teaching Developments in Hong Kong and Macao; (34) Bilingual Educational Programmes in Indian Schools: Addressing the English Language Needs of the Country; (35) English in Scandinavia--A Success Story? Sub-saharan Africa Recent Federal Education Policy in the United States; (36) English Teaching in Australia and New Zealand; and (37) English in England and Wales: Knowledge and Ownership. Finally, Part VI, contains conclusion recommendations for practice, policy and research